2013
DOI: 10.4314/gjds.v9i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Smoked And frozen fish consumption and marketing channels in the Tamale Metropolis of Ghana

Abstract: Fish marketing has become an important trade in Ghana due to the increasing appreciation of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
3
12
1
Order By: Relevance
“…This is not unrelated to the occasional consumption of this form of fish as it is mostly marketed in places of relaxation, entertainment or social gatherings, and is also more expensive than the other forms. The result is in line with the findings of Alhassan et al [14] in Tamale Metropolis of Ghana, where they found frozen/fresh fish type to be more preferred than smoked fish. It indicates that the demand and consumption outcomes for different forms of fish are place specific [15] and also depend on the relative preferences/attributes of the consumers.…”
Section: Quantity and Price Of Different Forms Of Fish Consumedsupporting
confidence: 92%
“…This is not unrelated to the occasional consumption of this form of fish as it is mostly marketed in places of relaxation, entertainment or social gatherings, and is also more expensive than the other forms. The result is in line with the findings of Alhassan et al [14] in Tamale Metropolis of Ghana, where they found frozen/fresh fish type to be more preferred than smoked fish. It indicates that the demand and consumption outcomes for different forms of fish are place specific [15] and also depend on the relative preferences/attributes of the consumers.…”
Section: Quantity and Price Of Different Forms Of Fish Consumedsupporting
confidence: 92%
“…2). The number of fish types obtained in the current study was far lower than reported by Alhassan et al [20]. Probably due to distance to the source of fish, leading to the limited choices of fish types by consumers in the Sunyani Municipality.…”
Section: Fish Speciescontrasting
confidence: 84%
“…Other potential influencing factors for smoked fish products was the flavor, taste and wholesomeness in stews and soups. Reasons identified for the consumption of smoked fish products conformed to findings by Alhassan et al [20] and [23].…”
Section: Fish Products Consumedsupporting
confidence: 83%
“…Fishery products contribute to food security either by providing nutrients (protein, lipids, polyunsaturated fatty acids, vitamins, iodine, iron, etc. ) to human body and by guaranteeing source of income for fishermen, processors, and countries (FAO (Food (Alhassan, Boateng, & Ndaigo, 2012;Chabi et al, 2014;Kpodekon et al, 2014;Kumolu-Johnson, Aladetohun, & Ndimele, 2010;Yakubu & Ngueku, 2015). According to Berkel, Boogaard, and Heijnen (2005), smoking is carried out according to three methods which are cold smoking (30°C), hot smoking (65-100°C) resulting in cooked but not dried product, and smoke drying at 45-85°C resulting in hot smoking followed by drying.…”
Section: Introductionmentioning
confidence: 99%
“…In Benin, traditional hot smoking and smoke drying are the smoking methods frequently performed by female processors and used to preserve fish (Assogba et al, 2019). Smoked fish products are consumed all over the world as protein source (Alhassan et al, 2012;Desiere, Hung, Verbeke, & D'Haese, 2018;Kiczorowska, Samolinska, Grela, & Bik-Małodzinska, 2019). Smoked fish has good nutritional quality including protein, lipid, and fatty acids (Kiczorowska et al, 2019;Nunoo, Tornyeviadzi, Asamoah, & Addo, 2019;Tiwo, Tchoumbougnang, Nganou, Kumar, & Nayak, 2019).…”
Section: Introductionmentioning
confidence: 99%